PERAN BUDAYA ORGANISASI MEMODERASI MOTIVASI KERJA TERHADAP KINERJA KARYAWAN BUMDES MORO BERKAH - Turmudhi, Anis; Prasetya, Adhitya Yoga; Praptitorini, Mirna Dyah (Jurnal Ilmu Manajemen dan Akuntansi Terapan (JIMAT), 2021)
This research aims to determine the effect of organizational culture that moderates the effect of work motivation on the performance of Moro Berkah Village Owned Enterprises (Bumdes) employees in Mororejo village, Kaliwungu, Kendal, Central Java. The background is from the relatively young age of the organization, as well as the unprofessional performance of Bumdes Moro Berkah employees. The independent variables in this study are work motivation and organizational culture as moderating variables. This research is a quantitative research, with data collection techniques through distributing questionnaires to 40 employees. The data analysis technique used simple linear regression analysis and moderated regression analysis (MRA). The results show that work motivation has a positive and significant effect on employee performance, and organizational culture strengthens the influence of work motivation on employee performance.